2024
DOI: 10.3389/fpubh.2024.1370635
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effects of attitude on the relationship between knowledge and willingness to organ donation among nursing students

Xiaohang Chen,
Xin Zhou,
Yan Xu
et al.

Abstract: BackgroundThe current rate of organ donation in China falls significantly below the global average and the actual demand. Nursing students play a crucial role in supporting and promoting social and public welfare activities. This study primary aims to analyze the levels of knowledge, attitudes, willingness toward organ donation, and attitudes toward death among nursing students, and investigate the mediating role of attitude in the relationship between knowledge and willingness. The secondary aims to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…[18][19][20][21][22] Interestingly, Terada et al [23] found less support for organ donation after brain death among nurses, a sentiment also observed among nursing students in a study by a Chinese team. [24] This suggests that while education and information access are important, additional factors influence attitudes towards organ donation. [25] In contrast, acceptance rates in the N-HS group in our study were similar to those reported by other studies.…”
Section: Discusionmentioning
confidence: 99%
“…[18][19][20][21][22] Interestingly, Terada et al [23] found less support for organ donation after brain death among nurses, a sentiment also observed among nursing students in a study by a Chinese team. [24] This suggests that while education and information access are important, additional factors influence attitudes towards organ donation. [25] In contrast, acceptance rates in the N-HS group in our study were similar to those reported by other studies.…”
Section: Discusionmentioning
confidence: 99%